Hubungan Human Resource Information System (HRIS) dan Human Resource Management (HRM): Telaah Literatur Sistematis - Siti Fatimah; Hamdani Hamdani (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2026)
This study aims to analyze the relationship between Human Resource Information System (HRIS) and Human Resource Management (HRM) using a Systematic Literature Review approach. The reviewed literature consists of scholarly articles published between 2021 and 2026 that discuss the role of HRIS in supporting human resource management functions across various sectors and regions. The findings indicate that HRIS plays an important role in improving HRM efficiency through administrative automation, employee data integration, and the acceleration of payroll, attendance, recruitment, training, and performance appraisal processes. In addition to its administrative functions, HRIS also strengthens the strategic role of HRM by providing accurate information for workforce planning, competency development, performance management, and data-driven decision-making. The effectiveness of HRIS is influenced by organizational readiness, management support, system quality, digital literacy, data security, and user acceptance. The findings also show that the benefits of HRIS vary depending on the industrial sector, organizational characteristics, and readiness of technological infrastructure. This study emphasizes that HRIS is not merely a digital tool, but also a strategic instrument that can enhance the quality of HRM when aligned with organizational needs and user capabilities.